CSR PRACTICES IN MALAYSIA: Trends and Development - Mohamad, Mohamad Hanap (Journal of Islam and Science, 2015)
Apart from corporate governance which is of priority among the shareholders and stakeholders, the issue of Corporate Social Responsibility (CSR) has been of growing concern to all members of society lately. This is because the current global economic and recent US financial crisis had severely impacted the global economy which served a good reminder. The consequences of the crisis not only made many investors around the world lost money but also caused many employees in US, Europe and to some extend in Asia lost their jobs permanently. The repercussions would hinder social progress as people have to live below their means to cope with higher cost of living. Meantime, irre- sponsible corporations that contributed directly or indirectly to global warming continued to threaten people’s living environment amidst of the above two issues.